Management of IS/ICT with focus on ICT services outsourcing - Šebesta, Michal; Voříšek, Jiří, 1950-; Havlíček, Zdeněk; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2016)
Research on outsourcing has been around for several decades, while recent evolution in the information systems discipline towards ICT service commoditization significantly changes the context of decision-making. Services that are available on-demand via the Internet allow organizations implementing functions they demand in a fraction of time. This trend represents a chance for organizations seeking to use advanced ICT services without a need of major investments. Problem is the current lack of guidelines and tools for managing ICT services and their outsourcing. Given the trends on the ICT service market, it is expected that much of the IT management in the future will encompass the ICT services and utilize service-level structures. Methods currently available are either too broad or encompass only small part of the whole problem. Ad-hoc or unsound decisions in this area might cause major complications in terms of quality, usability, integration, and consequently influence total cost of organizational IT. Organizations need to either revise existing models or propose and implement completely new models to manage their IS/ICT. This thesis deals with the management of IS/ICT with focus on the ICT services outsourcing. It discusses available sourcing models in the literature and links them to the various interconnected areas. Based on these areas, it presents an integrated view on IT outsourcing strategies. Most importantly the thesis proposes an original concept for decision-making about outsourcing of ICT services named the SOURCER framework. This approach utilizes the presented outsourcing strategies, and introduces a complex methodology and decision-making criteria that will assist organizations with selection of ICT services in order to maintain and manage a most suitable ICT service portfolio. The decision-making is based on four essential viewpoints: function, costs, time, and quality.
These viewpoints are discussed, individually analyzed, and serve as a basis for further research. The whole framework is developed and validated according to Design Science Research Methodology (DSRM). Individual components are evaluated using a survey among a group of selected IT managers. Proof of concept is then established by a case study on framework use in a real organization. This case study covers strategy specification, business--IT alignment, specifying service architecture and its interconnections, outsourcing, and management of the ICT service portfolio.
Vedoucí práce: Jiří Voříšek
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor disert. práce]; disertace; dissertations